From the Editor-in-Chief: Changes to Enhance the Author Experience - Samantha Elliott (American Society for Microbiology, 2014)
JMBE Editor-in-Chief, Dr. Samantha Elliott, thanks past volunteers for their efforts and discusses several new author enhancements related to the recently expanded scope, including video tutorials, a self-assessment tool, and a thematic issue.